Erratum: Effects of Zooplankton Extracts on the Production of Paralytic Shellfish Toxins by Gymnodinium catenatum and Alexandrium pacificum - Jae Yeon Park; Dong Han Choi; Na Yeong Kim; Myung Jin Hyun; Young-Eun Kim; Jae-Hoon Noh; Jung-Rae Rho; Bum Soo Park; Seongjin Hong; Sea-Yong Kim; Mungi Kim; Jeonghoon Han; et al. (Ocean Science Journal, 2025)

First evidence of Gymnodimine D in Alexandrium ostenfeldii strain K-1354 - Jun-Geon Je; Nari Seo; Jaeseong Kim; Chan-Young Kim; Hye Won Kim; Jae Young Yu; You-Jin Jeon; Hyun Woo Kim; Yun Jo Chung; Hyun Joo An; Jung-Rae Rho; Young-Sang Kim (Algae, 2025)
This study presents a comprehensive analysis of gymnodimine-series toxins produced by Alexandrium ostenfeldii (K- 1354) using liquid chromatography tandem mass spectrometry (LC-MS/MS). Three peaks with identical precursor ions but different retention times were observed, suggesting the presence of isomers identified as gymnodimines B, C, and D. Employing an integrated approach combining LC-MS/MS with electron transfer dissociation, the study revealed the characteristic fragment ions of gymnodimine D. Notably, this study demonstrated the potential for isolating and purifying gymnodimine D from culturable A. ostenfeldii, addressing the current lack of commercially available standards for this isomer. This study contributes remarkably to marine biotoxin monitoring and the understanding of these structurally complex compounds.

Effects of Zooplankton Extracts on the Production of Paralytic Shellfish Toxins by Gymnodinium catenatum and Alexandrium pacificum - Jae Yeon Park; Dong Han Choi; Na Yeong Kim; Myung Jin Hyun; Young-Eun Kim; Jae-Hoon Noh; Jung-Rae Rho; Bum Soo Park; Seongjin Hong; Sea-Yong Kim; Mungi Kim; Jeonghoon Han; et al. (Ocean Science Journal, 2024)

Interactions between the calanoid copepod Acartia hongi and the bloom-forming dinoflagellates Karenia bicuneiformis and K. selliformis - Jin Hee Ok; Hae Jin Jeong; Ji Hyun You; Sang Ah Park; Hee Chang Kang; Se Hee Eom; Moo Joon Lee; Jung-Rae Rho (Marine Biology, 2024)
Copepods are a major component of metazooplankton and important prey for fish and invertebrates such as crabs, shrimps, and flatworms. Certain bloom-forming dinoflagellates can kill copepods, but there is little research on the interactions between copepods and the bloom-forming dinoflagellates Karenia bicuneiformis and K. selliformis . In this study, the survival and ingestion rates of the calanoid copepod Acartia hongi feeding on K. bicuneiformis and K. selliformis were determined as a function of prey concentration. On day 2, the survival of A. hongi incubated with K. bicuneiformis was 90–100% at all the tested prey concentrations, while that with K. selliformis was 0–20% at ≥ 582 ng C mL −1 . Compared to other harmful dinoflagellates from the literature, K. bicuneiformis caused low mortality of Acartia ; however, K. selliformis caused almost the highest mortality at similar dinoflagellate concentrations. With increasing mean prey concentration, the ingestion rates of A. hongi feeding on K. bicuneiformis increased on day 1, but those on K. selliformis did not increase. Acartia hongi stopped feeding on K. bicuneiformis at mean prey concentrations of ≥ 341 ng C mL −1 and K. selliformis at all prey concentrations on day 2. At the prey concentration of 1000 ng C mL −1 , the ingestion rate of A. hongi feeding on K. bicuneiformis was moderate among the rates of Acartia spp. feeding on harmful dinoflagellates; however, that on K. selliformis was the lowest. These results indicate that K. bicuneiformis and K. selliformis differentially affect the survival and ingestion rates of A. hongi .

Sulfoquinovosylmonoacylglycerols regulating intestinal inflammation in co-culture system from the brown alga Turbinaria ornata - Seon Min Lee; Na-Hyun Kim; Yeong Kwang Ji; Yun Na Kim; You-Jin Jeon; Jeong Doo Heo; Eun Ju Jeong; Jung-Rae Rho (Algae, 2020)

Spatial and seasonal distributions of the phototrophic dinoflagellate Biecheleriopsis adriatica (Suessiaceae) in Korea: quantification using qPCR - Hee Chang Kang; Hae Jin Jeong; Jin Hee Ok; Ji Hyun You; Se Hyeon Jang; Sung Yeon Lee; Kyung Ha Lee; Jae Yeon Park; Jung-Rae Rho (Algae, 2019)

Intraspecific variations in macronutrient, amino acid, and fatty acid composition of mass-cultured Teleaulax amphioxeia (Cryptophyceae) strains - Bae Ik Lee; Shin Kwon Kim; Jong Hyeok Kim; Hyung Seop Kim; Jong Im Kim; Woongghi Shin; Jung-Rae Rho; Wonho Yih (Algae, 2019)

Mixotrophy in the sand-dwelling dinoflagellate Thecadinium kofoidii - Yeong Du Yoo; Kyeong Ah Seong; Jae Seong Kim; Seung Won Nam; Hae Jin Jeong; Jung-Rae Rho; Wonho Yih; Hyung Seop Kim (Marine Biology Research, 2018)

Fatty acid composition and docosahexaenoic acid (DHA) content of the heterotrophic dinoflagellate Oxyrrhis marina fed on dried yeast: compared with algal prey - Eun Young Yoon; Jaeyeon Park; Hae Jin Jeong; Jung-Rae Rho (Algae, 2017)

Erratum to: Accumulation of galloyl derivatives in a green alga, Spirogyra varians, in response to cold stress - Jong Won Han; Minchul Yoon; Frithjof C. Küpper; Tatyana A. Klochkova; Jung-Soon Oh; Jung-Rae Rho; Gwang Hoon Kim (Journal of Applied Phycology, 2013)

Accumulation of galloyl derivatives in a green alga, Spirogyra varians, in response to cold stress - Jong Won Han; Minchul Yoon; Frithjof D. Kupper; Tatyana A. Klochkova; Jung-Soon Oh; Jung-Rae Rho; Gwang Hoon Kim (Journal of Applied Phycology, 2012)

Metagenomic examination of diversity within eukaryotic plankton from the ulleung basin in the East Sea of Korea - Sang-Rae Lee; TaeKeun Rho; Jung Hyun Oak; Jin Ae Lee; Tongsup Lee; Ik Kyo Chung (Journal of Plant Biology, 2012)